Timescales of self-healing in human bone tissue and polymeric ionic liquids. Issue 3 (September 2014) - Akbarzadeh, Johanna; Puchegger, Stephan; Stojanovic, Anja; Kirchner, Helmut O. K.; Binder, Wolfgang H.; Bernstorff, Sigrid; Zioupos, Peter; Peterlik, Herwig
Abstract : Strain (stress-free) relaxation in mechanically prestrained bone has a time constant of 75 s. It occurs by a reorganization of the proteoglycan-glycoprotein matrix between collagen fibers, which requires ionic interactions. Dissolving and relinking the ionic bonds is thus an important tool of nature to enable plastic deformation and to develop self-healing tissues. A way to transfer this approach to technical materials is the attachment of ionic end groups to polymeric chains. In these classes of materials, the so-called polymeric ionic liquids, structural recovery of thermally disorganized material is observed. A time constant between minutes and a week could be achieved, also by ionic rearrangement. The same mechanism, rearrangement of ionic bonds, can lead to vastly different relaxation times when the ionic interaction is varied by exchange of the cationic end groups or the anions.